Tradición católica y modernidad funcional: El combate intelectual, y trágico, de Ramiro de Maeztu - Fernández Riquelme, Sergio (Mercurio Peruano, 2020)
Only few writers can represent more genuinely, more tragically, in their life history and the outlines of their thought, the "militancy of knowledge" as did Ramiro de Maeztu. This article discusses the Spanish thinker’s itinerary through the main cultural and intellectual battles, perhaps lost in the past, perhaps forgotten in the present, from his renewal economic proclamation to his project for the Hispanic world.